2018
DOI: 10.1021/acs.inorgchem.8b01020
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Co(II) Dominant and Oxygen Vacancy Defective CuCo2O4@CQDs Hollow Spheres for Enhanced Overall Water Splitting and Supercapacitor Performance

Abstract: The hierarchical CuCoO@carbon quantum dots (CQDs) hollow microspheres constructed by 1D porous nanowires have been successfully prepared through a simple CQDs-induced hydrothermal self-assembly technique. XPS analysis shows the CuCoO@CQDs possesses the Co(II)-rich surface associated with the oxygen vacancies, which can effectively boost the Faradaic reactions and oxygen evolution reaction (OER) activity. For example, the as-synthesized 3D porous CuCoO@CQDs electrode exhibits high activity toward overall electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…According to the X‐ray diffraction (XRD) patterns in Figure c, this carboneous product is amorphous and has no obvious effect on crystallization of NiCo 2 O 4 during the synthesis. Furthermore, as shown in Figure S4b (Supporting Information) the Ni 2p spectra consist of two spin–orbit doublets (2p 1/2 and 2p 3/2 ) and their shake‐up satellites, in which the fitting peaks at 854.4 and 871.9 eV are contributed to Ni 2+ as well as the other fitting peaks at 855.9 and 874.0 eV are indexed to Ni 3+ , respectively, confirming the presence of both Ni 2+ and Ni 3+ . Similarly, the Co 2p spectra in Figure S4c (Supporting Information) also consist of the contributions of Co 2+ (779.8 and 794.8 eV) and Co 3+ (780.8 and 796.0 eV), respectively …”
Section: Resultssupporting
confidence: 55%
“…According to the X‐ray diffraction (XRD) patterns in Figure c, this carboneous product is amorphous and has no obvious effect on crystallization of NiCo 2 O 4 during the synthesis. Furthermore, as shown in Figure S4b (Supporting Information) the Ni 2p spectra consist of two spin–orbit doublets (2p 1/2 and 2p 3/2 ) and their shake‐up satellites, in which the fitting peaks at 854.4 and 871.9 eV are contributed to Ni 2+ as well as the other fitting peaks at 855.9 and 874.0 eV are indexed to Ni 3+ , respectively, confirming the presence of both Ni 2+ and Ni 3+ . Similarly, the Co 2p spectra in Figure S4c (Supporting Information) also consist of the contributions of Co 2+ (779.8 and 794.8 eV) and Co 3+ (780.8 and 796.0 eV), respectively …”
Section: Resultssupporting
confidence: 55%
“…As shown in Fig. 3c, two obvious peaks of Co 2p 3/2 and Co 2p 1/2 can be split into two spin-orbit doublets, which can be assigned to Co 3+ (780.5 and 795.7 eV) and Co 2+ (782.1 and 797.4 eV), respectively [26,27]. Based on the peak area, the ratio of Co 2+ /Co 3+ on the surface of VO-rich Co 2 AlO 4 was determined to be 1.78, which was much higher than that of pristine Co 2 AlO 4 (0.84).…”
Section: Methodsmentioning
confidence: 95%
“…. ARTICLES (Table S1) [27,33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The results indicated that the VO-rich Co 2 AlO 4 possessed a high OER kinetics.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations